2020
DOI: 10.3390/toxics8010008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cannabinoid-Containing Fluids in Illicit Vaping Cartridges Recovered from Pulmonary Injury Patients: Identification of Vitamin E Acetate as a Major Diluent

Abstract: Beginning in June of 2019, there was a marked increase in reported cases of serious pulmonary injury associated with vaping. The condition, referred to as e-cigarette or vaping product use-associated lung injury (EVALI), does not appear to involve an infectious agent; rather, a chemical adulterant or contaminant in vaping fluids is suspected. In August of 2019, the Wadsworth Center began receiving vaporizer cartridges recovered from patients with EVALI for analysis. Having no a priori information of what might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
119
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 38 publications
1
119
0
1
Order By: Relevance
“…However, vaporizers have been recently associated with acute respiratory illness, now referred to as e-cigarette or vaping product-use associated lung injury (EVALI) [ 21 , 22 ]. The cause of this condition is currently under investigation, although there is evidence implicating the vitamin E acetate used as a diluent in vaporizer liquids [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, vaporizers have been recently associated with acute respiratory illness, now referred to as e-cigarette or vaping product-use associated lung injury (EVALI) [ 21 , 22 ]. The cause of this condition is currently under investigation, although there is evidence implicating the vitamin E acetate used as a diluent in vaporizer liquids [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have revealed that constituents of Eliquids with Vitamin-E (alpha-tocopherol) acetate (VEA) is the likely culprit in worsening respiratory failure in these patients [16][17][18]. Vaping is the process of inhaling an aerosol that is created by heating a liquid or wax containing various substances, such as nicotine, cannabinoids causing acute lung injury that can be lethal.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza associated rhabdomyolysis has been previously reported in case reports in literature [22][23][24][25][26][27][28][29][30][31]. Recent review of literature in 2015 revealed twelve case reports with CK levels ranging from 1317 to 1,127,000 with mean value of 206, 908, with survival of 83% [18]. An additional six cases have been reported in the literature since then [25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…The rapidly growing number of clinically reported cases of e-cigarette, or vaping, product useassociated lung injury (EVALI) since August 2019 has placed this as a major public health concern in the United States [1][2][3][4]. The US Centers for Disease Control and Prevention (CDC) reported on the 14 th of January 2020 that at least 2,668 hospitalized EVALI patients and 60 deaths had been recorded across the country [5].…”
Section: Introductionmentioning
confidence: 99%